Neglect of Parents at UPTD Social Services for the Elderly Binjai in Review of Islamic Law and UU No.1 of 1974 Concerning Marriage - Afifah Salsabila Lubis, Nurul; Syam, Syafruddin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The obligations of parents are the rights of children, and vice versa, the obligations of children towards their parents are the rights of the children's parents. Namely, parents are obliged to care for and provide guidance to their children who are not old enough according to their respective abilities. Family law seeks to regulate relationships between families. In this research, the author conducted research on parental neglect at the Binjai Elderly Social Services UPTD in terms of Islamic Law and UU No. 1 of 1974 concerning Marriage which the researcher took from the case study of Parental Neglect at the Binjai Elderly Social Service. Update. This legal research uses a normative-empirical approach. The type of research used is descriptive, namely research that generally aims to systematically, factually, and accurately describe a problem that has occurred. The data source that the author uses in this research is primary data obtained by the author directly from interviews. The data validity testing technique in this research uses data triangulation. Islam emphasizes the importance of caring for parents as a form of filial piety. The Qur'an commands children to be kind to their parents, even when they reach old age. Article 46 states the rights and obligations of children towards their parents, which states that children are obliged to respect and obey the good wishes of their parents, and when a child is an adult, they are obliged to support their parents and support family members at home. best, if they need help.